Examining the impact of soft news and social media use on political knowledge of the Chinese younger generation - Qiu, Ruochen (Kansas State University, 2011)
Since the 1990s, much discussion about the rise of the Internet within the People’s Republic of China has focused on the political consequences of the technology on China’s Communist Party. The popularization of Internet access was once regarded as a sign of significant progress in Chinese political democratization. Especially when considering the impact of Internet use on the Chinese younger generation, the importance of political issues spread through Internet should be more amplified. One interesting phenomenon that needs attention is the emergence of political soft news in recent years on the Chinese national social network that never arose before in the history of the People’s Republic of China. Different from any type of solemn formal political news that appeared in Chinese media, the soft news tends to emphasize entertaining aspects of political issues more and engages with high readability. It pays more attention to the gender, personality, and appearance--even the daily life of the leaders who were once the most mysterious and paramount group in Chinese political system. One important trait of this kind of news is that most news items emerged in social networks and websites that young adults are frequently exposed to. Along with the rapid rise of Chinese social media, will the major participants, Chinese young adults be strongly influenced by political soft news spread through the Internet? Will the young adults be attracted by the soft news initially and then try to know some further information about the government’s policies? Or, will they only dwell on the soft news? This research tries to explore and provide answers to these questions and focus on the impact of the soft news on Chinese young adults’ understanding of politics.
Keywords: Chinese political soft news; Social media; Political knowledge; Democracy; Mass Communications (0708)